The Effect Of Audit Committee Financial Expertise And Relative Status On Earnings Management: Case Of Indonesia - Delfita Siagian; Sylvia Veronica Siregar (Fakultas Ekonomi dan Bisnis Universitas Tarumanagara, 2018)
The aim of this research is to examine the effect of audit committee financialexpertise (measured by audit committee experience in accounting, supervision, andfinancial)and audit committee status (relative to management) on earnings management.Our samples consist of 384 observations in Indonesia Stock Exchange for the year 2012-2014. The result of this research shows that audit commite financial expertise has nosignificant effect on earnings management. However, we find evidence that auditcommittee financial expertise haspositive effect on income decreasing accruals. Thisfinding indicates that audit committee may perceived that conservatism is one of themechanism to restrict management opportunistic behavior. We do not find significantevidence of the joint effect of audit committee status and audit committeee expertise onearnings management.